Comparative Study of Modulation-Based Individual Inverter Techniques for Direct and Inverse by using Star-Connection Induction Motor in Extra Low Voltage Application - Wishnuprakasa, Ardhia; Purwanto, Era; Windarko, Novie Ayub (EMITTER International Journal of Engineering Technology, 2016)
In this study, the IEEE 519 Standard as a basis benchmarking for voltage (THDV) and current (THDI) in draft performance. Comparative Study based onthree-techniques of 2-Level Converter (2LC) by using a Star-Connection Induction Motor (Y-CIM) in ExtraLow Voltage (ELV) Configuration.For the detail explanation, a primary inverter as Direct-Inverterby PWMdirect (PWM) degreesand asecondary inverter as Inverse-Inverterby PWMinverse(PWM + PI) degrees. It tends a modified algorithm,for eachof SPWM in six rules, and FHIPWM in 5th harmonics Injectedin standard modulation as the purpose for the Open-Ends of Pre-Dual Inverter in Decoupled SPWM for twelve rules, and Decoupled FHIPWM in combination of 5th harmonics Injectedin combination of two-standard-modulation. Those techniques are the purpose of two-inverter combination, which namelythe Equal Direct-Inverse (EDI) algorithmproduct of prototyping in similarities. The observation is restricted in voltage scope between Simulation by using Power Simulator (PSIM)and Application by using Microcontroller ARM STM32F4 Discovery.